Primary Biliary Cirrhosis Associated with Systemic Sclerosis: Diagnostic and Clinical Challenges. (6th December 2011) - Rigamonti, Cristina; Bogdanos, Dimitrios P.; Mytilinaiou, Maria G.; Smyk, Daniel S.; Rigopoulou, Eirini I.; Burroughs, Andrew K.
Abstract : Patients with primary biliary cirrhosis (PBC) often have concurrent limited systemic sclerosis (SSc). Conversely, up to one-fourth of SSc patients are positive for PBC-specific antimitochondrial antibodies (AMA). The mechanisms responsible for the co-occurrence of these diseases are largely unknown. Genetic, epigenetic, environmental, and infectious factors appear to be important for the pathogenesis of the disease, but the hierarchy of events are not well defined. Patients with SSc and PBC have an increased morbidity and mortality compared with the general population, but whether the presence of both diseases in an affected individual worsens the prognosis and/or outcome of either disease is not clear. Some case reports suggested that the presence of SSc in PBC patents is associated with a more favorable prognosis of the liver disease, whereas others report an increased mortality in patients with PBC and SSc compared to patients with PBC alone. This paper discusses the features of patients with PBC-associated SSc. Our aims are to clarify some of the pathogenetic, diagnostic, and clinical challenges that are currently faced in the routine management of these patients. We also intend to provide some practical hints for practitioners that will assist in the early identification of patients with PBC-associated SSc.